Fish is a perishable product, and thereby needs a special treatment to prolong its shelf life. Traditionally, drying is a common treatment for the purpose, especially by using sun drying. This paper is devoted to the study of histiophoridae fish drying using a truneated trapezoidally shaped green house effect solar dryer in order to maximize the use of solar energy. The drying system used different size of racks and tray following the dimension of the structure so as to minimize empty space. - Binsar Nababan; Kamaruddin Abdullah; Armansyah H. Tambunan; A Harsono Soepardjo (Forum Pasca Sarjana, 2007)
Fish is a perishable product, and thereby needs a special treatment to prolong its shelf life. Traditionally, drying is a common treatment for the purpose, especially by using sun drying. This paper is devoted to the study of histiophoridae fish drying using a truneated trapezoidally shaped green house effect solar dryer in order to maximize the use of solar energy. The drying system used different size of racks and tray following the dimension of the structure so as to minimize empty space. The dryer was equipped with 25 watt DC blowers to remove the moist air. From two experimental runs, the results show that the system can properly dry the histiophoridae fish to its desired moisture content, which ranged from 30.08% (wb) to 32.80% (wb). Utilization of the truneated trapezoidally shaped green house effect solar dryer was found to be effective in enhancing the absorbtion of solar irradiation not only by the heat absorber but also by the producs on speated the vertically arranged racks. Solar PV modules were used to power inlet exhaust fans as well as for temperature control. A PCM energy storage was also provided to provide heating during night time. Keywords: fish drying, trapezoidal shape green house, solar drying, PCM heat storage, PV modul temperature control